2014
DOI: 10.1177/1090198114529128
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Nutritional Knowledge and the Amount of Sugar-Sweetened Beverages Consumed in Los Angeles County

Abstract: Although consumption of sugar-sweetened beverages (SSBs) is associated with many negative health outcomes, including obesity, diabetes, and cardiovascular disease, the relationship between consumer nutritional knowledge and the amount consumed is poorly understood. The objective of this study was to examine the relationship between knowledge of daily calorie recommendations and the amount of SSBs consumed in a large, economically and racially diverse sample of adults recruited at selected Metro subway and bus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 30 publications
4
38
0
2
Order By: Relevance
“…There was also an awareness that “excess” consumption increased health risks but there was little understanding of what constituted excess consumption, superficial understanding of documented health risks, and a perception among young adults in particular that health effects were neither proximal nor relevant. These findings are consistent with quantitative studies conducted in Australia and the US which indicate regular consumption of SSBs, but low awareness of health risks and sugar content …”
Section: Discussionsupporting
confidence: 91%
“…There was also an awareness that “excess” consumption increased health risks but there was little understanding of what constituted excess consumption, superficial understanding of documented health risks, and a perception among young adults in particular that health effects were neither proximal nor relevant. These findings are consistent with quantitative studies conducted in Australia and the US which indicate regular consumption of SSBs, but low awareness of health risks and sugar content …”
Section: Discussionsupporting
confidence: 91%
“…Six cross-sectional studies (Fadupin, Ogunkunle, & Gabriel, 2014;Gase, Robles, Barragan, & Kuo, 2014;Huffman & West, 2007;Lee & Joo, 2016;Park, Onufrak, Sherry, & Blanck, 2014;Zytnick, 2015) and one case-study (Nelson & Hekmat, 1991) investigated the association between knowledge about sugar and sugar intake. Three of these cross-sectional studies (Gase et al, 2014;Lee & Joo, 2016;Park et al, 2014) reported an association between increasing knowledge about sugar and reduced consumption of food and beverages with sugar. These findings were consistent across studies conducted in two different countries (Korea and US), with varying sample sizes (n=250, 1041 and 3926) and using different data collection tools.…”
Section: Methodological Quality Of Included Studiesmentioning
confidence: 99%
“…Adequate nutrition knowledge is one building block for making healthy dietary decisions [7]. For example, providing caloric information on sugar-sweetened beverages has led to attitude changes [8] and reduced purchases [9].…”
Section: Introductionmentioning
confidence: 99%